Letrozole-Induced Polycystic Ovary Syndrome Attenuates Cystathionine-β Synthase Gene Expression in the Ovaries of Female Sprague Dawley Rats. (29th May 2020) - Bries, Amanda; Webb, Joe; Vogel, Brooke; Carrillo, Claudia; Keating, Aileen; Schalinske, Kevin
Abstract: Objectives: Polycystic ovary syndrome (PCOS) is an endocrine disorder that affects 10% of reproductive age women and leads to hyperandrogenism, abnormal menstrual cycles, and polycystic ovaries. Moreover, PCOS has been associated with elevated serum homocysteine; however, the characterization of one-carbon metabolism (OCM) in PCOS remains incomplete. The aim of our research was to examine OCM in a genetic and chemically-induced rodent model of PCOS: 1) viable yellow Agouti (Avy) mice; and 2) letrozole (Let)-induced Sprague Dawley (SD) rats. Methods: Five wk old female Avy mice ( N = 18), their lean controls ( N = 18), and SD rats ( N = 36) were acclimated for one wk. Following acclimation, the animals were placed on a modified standard AIN93G diet (energy, %: 50.4, carbohydrate; 17.3, protein; and 32.3, fat). Rats were randomly assigned to Let (1 g/kg BW) treatment or vehicle (carboxymethylcellulose) control that was administered via a subcutaneously implanted slow-release pellet every 30-d. For both models, 12 animals were randomly assigned to be euthanized during proestrus at one of the following ages: 8, 16 or 24 wk. Bodyweight and estrous cycles were measured daily. Ovaries were collected to assess gene expression of OCM. These data were analyzed using linear mixed models to determine the main effects of age and treatment at a significance level of P < 0.05. Results: Letrozole significantly reduced the occurrence of proestrus and estrus stages ( P = 0.0001 and P = 0.006, respectively). Additionally, Let-induced rats had increased BW compared to control rats, across all age groups ( P < 0.0001). In contrast, Avy mice weighed less than their controls by 24 wk of age ( P < 0.0001). Cystathionine-β synthase ( CBS ) mRNA expression was downregulated in the Let-induced vs. control rats at 16 (59%; P < 0.05) and 24 (77%; P < 0.01) wk of age. As expected, Cyp19A1, aromatase mRNA was downregulated in the Let-induced rats ( P = 0.02). Interestingly, betaine-homocysteine s-methyltransferase ( BHMT ) mRNA increased as a function of age in Let-induced rats ( P = 0.03). Conclusions: These data demonstrate that Letrozole-induced PCOS temporally decreases ovarian CBS mRNA expression; whereas, BHMT mRNA is upregulated as a function of age. Funding Sources: This work was supported by the National Institute of Child Health and Human Development.